Role of the speech therapy cabinet in the educational inclusion of young university students with a diagnosis of stuttering - Benavente-Vera, Sandra Úrsula (2021)
The research entitled CODI Program for thedevelopment of digital competences of teachers of the I.E. N ° 1129, La Victoria, 2020, aimed to demonstrate the effectiveness of its application in the development of digital skills, for which it used a quantitative methodology of experimental design with four treatments and a population made up of teachers from the educational institution. The reliability analyzes of the data collected with the validated instruments made it possible to demonstrate its reliability at high levels, data that were applied toa pilot sample. The applied statistics was from Anova of a factor that allowed to obtain results after the induction and training process has been carried out, which has allowed to demonstrate the effectiveness of the CODI program in the development of the digital competences of teachers of the I.E. N ° 1129, La Victoria, 2020, with the application of four treatments in an experimental design, and that the statistical analysis used indicates the growth of their learning.